Opaque Minerals in the Yamato-74191 Chondrules - Kimura, Makoto; Yagi, Kenzo; Onuma, Kosuke (1980)
P(論文) Opaque minerals occur often as phenocrysts in porphyritic chondrules. Troilite is common in comparison with metallic iron in chondrules, and is often distributed separately from metallic iron in a chondrule. Since some opaque minerals are included in silicate minerals, opaque minerals had crystallized in a chondrule before the crystallization of silicate minerals. Rare chromites are always in contact with troilites. These chromites, including some other meteoritic chromites, have cation deficiency in the B site. This cation deficiency may be interpreted by a substitution of 3Fe^<2+>=2Cr^<8+>+Vacancy. Chromites and olivines in chondrule crystallized in disequilibrium to each other. departmental bulletin paper